Порушення серцевого ритму у пацієнтів із цукровим діабетом 2-го типу та інфарктом міокарда - Карпенко, О. І.; Карпенко, О. О.; Безуглова, С. В.; Мицкевич, Л. В.; Злова, Т. І. (Clinical Endocrinology and Endocrine Surgery, 2014)
The article presents the results of a retrospective analysis of medical records of patients who underwent Q-myocardial infarction depending on the presence or absence of diabetes as well as on the level of glycated hemoglobin. It was shown that patients with a HbA1c <7% had more frequent supraventricular cardiac arrhythmias and hyperglycemia often leads to the development of ventricular cardiac arrhythmias.